AB0892 Evaluation of Thyroid Function in Children with Familial Mediterranean Fever. (10th June 2014) - Dortbas, F.; Kilicbay, F.; Cebeci, N.; Tufekci, O.; Comak, E.; Melek, E.
Abstract : Background: Familial Mediterranean fever (FMF) is the most frequent hereditary autoinflammatory disease, characterized by recurrent self-limited attacks of fever and polyserositis. The development of renal amyloidosis type AA is the most devastating manifestation of the disease. Apart from major target organs as renal, cardiovascular, respiratory and gastrointestinal system, endocrine organs can also be involved. Yet, it is unclear how FMF affects thyroid function in patients that are not complicated with amyloidosis. Objectives: The aim of this study was to evaluate the thyroid function in children with FMF that are not complicated with amyloidosis. Methods: A cross-sectional study was carried out in pediatric rheumatology outpatient clinics. The medical records of patients with FMF were reviewed. Demographic characteristics, disease duration, mutation analysis, clinical findings, free T3, free T4, TSH were all noted at attack free periods. Results: A total of 82 children, 42 girls (51.2%), with a mean age of 7.76±3.76 years at diagnosis and disease duration 22.31±24.42months, were included. Twenty one (25.6%) patients were found to have parental consanguinity and 31 (37.8%) patients had family history of FMF. Twelve (14.6%) patients were homozygous, 25 (30.5%) patients were compound heterozygous and 34 (41.5%) patients were heterozygous for MEFV gene. Eleven (13.4%) patients had complex allele mutations (≥3 mutations). Colchicine treatment was started in all patients. The dosage of colchicine needed to control the disease symptoms was 0.95±0.31 mg/day. The mean serum free T3, free T4 and TSH levels of patients were 3.96±0.54 pg/ml, 1.15±0.15 ng/ml, and 2.53±2.25 micU/ml, respectively. Hypothyroidism requiring levothyroxine treatment was found in 2 patients (2.43%) at the time of the study and one patient was found to have subclinical hypothyroidism. Conclusions: Although an association of hypothyroidsim and FMF has been reported before we did not find an increase prevalance of thyroid function abnormalities in children with FMF who are not complicated with amyloidosis. Our results suggest that thyroid function tests don't need to be screened routinely in FMF patients. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5111